EVALUASI TERHADAP KEMAMPUAN KADER KESEHATAN DALAM MELAKUKAN KEGIATAN PENJANGKAUAN - Ulfah, Nur; Budiaji, Budiaji; Harwanti, Siti (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2017)
Work accident on palm tappers can occur due to a dangerous state (unsafe codition) and unsafe acts (unsafe action). Efforts to prevent unsafe behaviors necessary to reduce the risk of such accidents with human approach, that of health cadres. The role of health cadres in this regard is to provide information to the safety behavior palm tappers. Meanwhile, cadres ability can be improved through a mentoring program.This research is a Quasi Experiment without comparison. The sample in this study is a health worker in the village Pageraji, Langgongsari, and RancamayaCilongok District of Banyumas regency as many as 30 people. The research instrument was a questionnaire and checklist. Data analysis to look at differences in pretest and posttest using the Wilcoxon test.Results of statistical analysis Wilcoxon test showed an increase of knowledge, attitudes and skills significantly after assistance, with the results of the knowledge value of p = 0.04 <? (0.05), the results of the analysis of the attitude of the value of p = 0.00 <? (0, 05), the results of the analysis of skills p = 0.00 <? (0.05).There is an increased knowledge, attitudes and skills significantly after mentoring.